The effect of time-window constraints and fleet size on the cost of a distribution operation - Barham, P. A. J. (Cranfield University, 1991)
Adopting a Continuous Space Modelling-type scenario of no detailed data being available at a customer-specific level, and on the basis, therefore, of basic information on delivery-area size, total number of locations to be visited and average road-speeds etc., quantitative expressions are derived for, the relationship between the number of vehicles operating from a central depot and the total fleet mileage that is required to visit a set of locations, and, 2. the effect of time-window constraints on the total cost of a similar operation. These expressions are derived using a simulation-based methodology, involving the setting-up of a computer program which both generates Travelling-Salesman tours and provides information on these tours at a detailed, disaggregated level. In the time-constrained context, it was necessary to develop a heuristic route-building procedure for solving Travelling-Salesman Problems due to the algorithmic